Answer:
V=16
Step-by-step explanation:
We are given that an inverse variation
![p=\frac{8}{V}](https://tex.z-dn.net/?f=p%3D%5Cfrac%7B8%7D%7BV%7D)
We have to find the value of V when p=1/2
To find the value of V we will substitute the value of p
Substitute the value of p
Then, we get
![\frac{1}{2}=\frac{8}{V}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%3D%5Cfrac%7B8%7D%7BV%7D)
![\frac{V}{2}=8](https://tex.z-dn.net/?f=%5Cfrac%7BV%7D%7B2%7D%3D8)
Using multiplication property of equality
![V=8\times 2](https://tex.z-dn.net/?f=V%3D8%5Ctimes%202)
Using multiplication property of equality
![V=16](https://tex.z-dn.net/?f=V%3D16)
Hence, the value of V=16
Answer:
![\boxed{2 {x}^{2} - 11x + 11}](https://tex.z-dn.net/?f=%20%5Cboxed%7B2%20%7Bx%7D%5E%7B2%7D%20%20-%2011x%20%2B%2011%7D%20)
Step-by-step explanation:
![= > ( {x}^{2} - 11x + 6) + ( {x}^{2} + 5) \\ \\ = > {x}^{2} - 11x + 6 + {x}^{2} + 5 \\ \\ = > {x}^{2} + {x}^{2} - 11x + 6 + 5 \\ \\ = > 2 {x}^{2} - 11x + 11](https://tex.z-dn.net/?f=%20%3D%20%20%3E%20%28%20%7Bx%7D%5E%7B2%7D%20%20-%2011x%20%2B%206%29%20%2B%20%28%20%7Bx%7D%5E%7B2%7D%20%20%2B%205%29%20%5C%5C%20%20%5C%5C%20%20%3D%20%20%3E%20%20%7Bx%7D%5E%7B2%7D%20%20-%2011x%20%2B%206%20%2B%20%20%7Bx%7D%5E%7B2%7D%20%20%2B%205%20%5C%5C%20%20%5C%5C%20%20%3D%20%20%3E%20%20%7Bx%7D%5E%7B2%7D%20%20%2B%20%20%7Bx%7D%5E%7B2%7D%20%20-%2011x%20%2B%206%20%2B%205%20%5C%5C%20%20%5C%5C%20%20%3D%20%20%3E%202%20%7Bx%7D%5E%7B2%7D%20%20-%2011x%20%2B%2011)
Answer:
Total cost of Theo's purchases in terms of k and p=2.49(k + p) + 5.99
Step-by-step explanation:
Cost of k key chain=$2.49
Cost of p photo frames=$2.49
Cost of a T-shirt=$5.99
Total cost of all items=cost of k key chain + cost of p photo frame + cost of The shirt
=2.49k + 2.49p + 5.99
Factorise
2.49 is common to both k and p
=2.49(k + p) + 5.99
Total cost of Theo's purchases in terms of k and p=2.49(k + p) + 5.99
Your mom your mom your mom your dad your mom
Answer:
option-C
Step-by-step explanation:
We are given row-echelon form
So, we can write equation from matrix as
![x-5z=-3](https://tex.z-dn.net/?f=x-5z%3D-3)
![y-4z=-5](https://tex.z-dn.net/?f=y-4z%3D-5)
Let's assume
![z=t](https://tex.z-dn.net/?f=z%3Dt)
now, we can find x and y
![x-5t=-3](https://tex.z-dn.net/?f=x-5t%3D-3)
![x=5t-3](https://tex.z-dn.net/?f=x%3D5t-3)
![y-4t=-5](https://tex.z-dn.net/?f=y-4t%3D-5)
![y=4t-5](https://tex.z-dn.net/?f=y%3D4t-5)
so, we get solutions as
![x=5t-3](https://tex.z-dn.net/?f=x%3D5t-3)
![y=4t-5](https://tex.z-dn.net/?f=y%3D4t-5)
![z=t](https://tex.z-dn.net/?f=z%3Dt)
where t can be any real numbers